A Newly Designed Water Soluble Uranyl‐Salophen Complex for Anion Recognition. Issue 8 (24th August 2021) - Forte, Gianpiero; Maglione, Maria S.; Tulli, Ludovico G.; Fantoni, Alessia; Dalla Cort, Antonella
Abstract: A novel water‐soluble uranyl‐salophen (salophen= N, N' ‐disalicylidene‐ o ‐phenylenediaminate) complex was obtained. Solubility was achieved in aqueous methyl‐β‐cyclodextrin solutions, taking advantage of the host‐guest interactions established with the adamantyl moieties present on the ligand skeleton. Such an approach facilitates the synthesis of the receptor and the purification processes and, in perspective, can be definitely applicable to other molecular scaffolds. UV/Vis titration experiments demonstrate that the capacity of the uranyl‐salophen core to behave as a receptor for anions is retained in water and appears comparable with that previously reported for other water‐soluble uranyl‐salophen systems. Hence the presence of cyclodextrins does not interfere with molecular recognition processes. Abstract : The first example of a lipophilic uranyl salophen complex decorated with adamantyl substituents that becomes soluble in water through the formation of inclusion complexes with methyl‐β‐CD. Its ability to behave as an anion receptor is retained in this medium and is not affected by the presence of CD excess.